MODELS OF ECONOMIC DEVELOPMENT TRENDS’ SOCIAL ORIENTATION IN THE INNOVATIVE PROCESSES’ GLOBALIZATION CONTEXT (Journal of Information Technologies in Education (ITE), 2012)
In the article real ways of national welfare as the innovative economic development integrated resource’ methodology and set of instruments revision are exposed, conditions, principles and factors of the national welfare new model as form of economic subjects interests coordination are conducted.
Keywords: innovative rent; intellectual and social resources combination; national welfare; innovations as the new form of productive